The Defining of the Meaning of the Truth in the Hebrew Bible in the Perspective of the Terms Semantically Connected with ’Emet and ’Emunah - Wójcik, Andrzej S. (Folia Philosophica, 2002)
The present article, together with the already published texts An Attempt at a Definition of the Truth in the Hebrew Bible on the Basis of its Opposites (“The Silesian Historical and Theological Studies” 2000, no. 33. pp. 104-126), and An Attempt at a Definition of the Truth in the Old Testament (“Polonia Sacra” 2001, in print since July 2000), constitutes a part of a larger whole devoted to the understanding of the truth in the Hebrew Bible (further on referred to as HB). This article, as opposed to the other ones, does not define the notion of truthfulness either by means of negating the meaning of the Hebrew terms which in HB are opposed to the truth, or in a “direct” way, i.e. by means of analysing the meaning of 38 Hebrew terms which appear in Polish translations of HB as: prawda (the truth), prawdziwy (true), prawdomówny (truthful), prawdziwie (truly), or doprawdy, naprawdę, zaprawdę (forsooth, in truth, verily). The author concentrates instead on achieving his purpose by examining the terms synonymous with the nouns ’emet, and ’emunah which carry in themselves the idea of truthfulness. The criterion on the basis of which synonymity is discovered consists in the existence of semantic links demonstrated, for example, by mutual substitution, parallelism, connecting with the help of conjunction, or hendiadys. Thus the results of the author’s research cast some light on the meaning of the idea of “truthfulness” in HB in a third way, independent from the two former ones. Owing to the research devices used here, we are going to be able to define precisely the meaning of ’emet and ’emunah, which should be achieved on five levels (from the most detailed to the most general): 1) directly by examining the meaning of the terms semantically connected with the above mentioned ones; 2) on the basis of the meaning of the Hebrew roots from which the discussed terms are derived; 3) through the meaning of the aspects under the heading of which the said terms may be linked on the basis of the criterion of synonimity; 4) by the meaning of the terms that appeared as a result of combining synonymous aspects; and 5) by the meaning of the groups of such dimension. On each of the above levels, apart from the content of the analysed terms (roots, aspects, and dimensions), we are going to establish the sequence of their appearance and proportions, which will make it possible to compare the results of the research on truthfulness in HB obtained in all three above mentioned ways. As far as the author knows, such an analysis that would include the whole of HB has not yet been carried out, and, even though in some studies it is possible to find statements emphasising the importance of such research, in none of them will we find a comprehensive analysis of the phenomenon, and all of them taken together do not offer any synthetic conclusions.